The Korean Peninsula in transition - Kim, Daw Hwan (New York : St. Martin's Press, 1997)
In association with St. Anthony's College
Keywords: Korea (South) -- Economic conditions -- 1960-.; Korea (South) -- Economic policy -- 1960-.; Korea (South) -- Foreign relations; Korea -- Economic conditions -- 1945-.; Korea -- Economic policy; Korea -- Foreign relations